2021
DOI: 10.1186/s42522-021-00048-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and epidemiological distribution of selected foodborne pathogens in human and different environmental samples in Ethiopia: a systematic review and meta-analysis

Abstract: Bacterial Foodborne Pathogens (FBP) are the commonest cause of foodborne illness or foodborne diseases (FBD) worldwide. They contaminate food at any stages in the entire food chain, from farm to dining-table. Among these, the Diarrheagenic Escherichia coli (DEC), Non typhoidal Salmonella (NTS), Shigella spp. and Campylobacter spp. are responsible for a large proportion of illnesses, deaths; and, particularly, as causes of acute diarrheal diseases. Though existing studies indicate the problem may be severe in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 118 publications
0
20
0
Order By: Relevance
“…C. Sappan L. extracts (E70T70) at 100 and 200 µg/mL significantly reduced (p < 0.05) the number of S. aureus and S. Enteritidis and reduced 100% at 24 h of the incubation period, while C. Sappan L. extracts at 200 µg/mL significantly reduced (p < 0.05) the number of E. coli and V. parahaemolyticus at 100% at 24 h of the incubation period. S. aureus, E. coli, Salmonella, Shigella, and Vibrio were identified as the most prevalent foodborne pathogens [37][38][39]. However, the prevalence rates could be related to the difference in time, location, and research season [37].…”
Section: Antimicrobial Activity Of C Sappan L Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. Sappan L. extracts (E70T70) at 100 and 200 µg/mL significantly reduced (p < 0.05) the number of S. aureus and S. Enteritidis and reduced 100% at 24 h of the incubation period, while C. Sappan L. extracts at 200 µg/mL significantly reduced (p < 0.05) the number of E. coli and V. parahaemolyticus at 100% at 24 h of the incubation period. S. aureus, E. coli, Salmonella, Shigella, and Vibrio were identified as the most prevalent foodborne pathogens [37][38][39]. However, the prevalence rates could be related to the difference in time, location, and research season [37].…”
Section: Antimicrobial Activity Of C Sappan L Extractsmentioning
confidence: 99%
“…The cell membrane structure of bacteria is related to the different resistance levels to antibiotics, dyes, detergents, and disinfectants [40,41]. Gram-positive bacteria have thicker outer peptidoglycan layers that absorb antibiotics and disinfectants more readily, making them S. aureus, E. coli, Salmonella, Shigella, and Vibrio were identified as the most prevalent foodborne pathogens [37][38][39]. However, the prevalence rates could be related to the difference in time, location, and research season [37].…”
Section: Antimicrobial Activity Of C Sappan L Extractsmentioning
confidence: 99%
“…78 Another review studies have also identified foodborne pathogens (Salmonella spp., pathogenic E. coli, Shigella spp., and Campylobacter spp) (11%) were extracted from samples (meat and meat products, dairy and dairy products, poultry products, and food contact surfaces). 86 The consumption of animal products such as meat, dairy and eggs, as well as vegetable products (fruits and vegetables), is increasing due to rapid population expansion, urbanization, increasing income per capita income, globalization and changes in consumption habits. [70][71][72][73] Thus, the risk of the spread of emerging and re-emerging antibiotic resistance is increased by human-animal-ecosystem interactions and causes deaths and economic losses each year.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…Foodborne pathogens continue to cause many intestinal diseases in humans around the world, causing a huge health and economic burden ( Ling et al, 2019 ; Akter et al, 2021 ; Prata et al, 2021 ; Qiu et al, 2021 ). Figures from the World Health Organization (WHO) estimate that about 2 billion people die each year from diarrhea or disease caused by contaminated food, and 30% of them are children under 5 years of age ( Scallan Walter et al, 2020 ; Belina et al, 2021 ; Van Puyvelde et al, 2021 ). The United States has one of the safest food supplies in the world, yet one in four people gets sick from foodborne diseases every year ( Hoffmann and Walter, 2020 ; Hoffmann et al, 2021 ; Ge et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%